1993
DOI: 10.1063/1.353071
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence due to lattice-mismatch defects in ZnTe layers grown by metalorganic vapor phase epitaxy

Abstract: Two sharp and intense emission bands with the maxima of 2.185 and 2.150 eV and a weak phonon coupling were investigated in the heteroepitaxial ZnTe layers. The study of the ZnTe layers grown on different substrates with thicknesses of 0.5–3.2 μm has shown that this luminescence is produced in the interface region that contains a high density of structural defects. The temperature dependence of these bands reveals the excitonic character of the recombination. We propose that the observed bands originate from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 18 publications
4
14
0
Order By: Relevance
“…50 meV below the free A-exciton transition energy. These findings remind very much on the Y-lines observed first by Dean et al in ZnSe [40], later observations were made by Naumov et al [34] and Fujii et al [41] in ZnTe. Note that the 3.41 eV emission in GaN also belongs to this class of recombination type [42].…”
Section: ˚C Annsupporting
confidence: 75%
See 2 more Smart Citations
“…50 meV below the free A-exciton transition energy. These findings remind very much on the Y-lines observed first by Dean et al in ZnSe [40], later observations were made by Naumov et al [34] and Fujii et al [41] in ZnTe. Note that the 3.41 eV emission in GaN also belongs to this class of recombination type [42].…”
Section: ˚C Annsupporting
confidence: 75%
“…It was, therefore, our interest to gain further insight into the nature of those recombinations using temperature dependent photoluminescence as well as spatially resolved cathodoluminescence. Our conclusion is that the lines sharp at around 3.333 eV is of excitonic nature and show most of the established features of the Y-line (excitons bound to structural defects) recombination commonly be seen in ZnSe and ZnTe [34,35]. Other lines between 3.31 and 3.33 eV belong to two-electron satellite transitions of the neutral donor bound exciton recombinations [33,36].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similar observations of excitonic recombinations at structural defects have also been reported in many other II-VI and III-V semiconductors such as ZnTe, CdTe, ZnS, CdS, GaN, and GaP. 41,46,[105][106][107] Naumov et al 105 discovered that the intensity of Y line emissions in ZnTe epilayers is a function of the lattice mismatch between layer and substrate and concluded that the observed luminescence is related to recombinations of excitons bound to extended structural defects which should be represented by misfit dislocations. Similar transition lines were also found in CdTe which were attributed to excitons bound to structural defects such as twins, dislocations, or stacking faults.…”
Section: K Defect Bound Excitons In Other Compound Semiconductorssupporting
confidence: 57%
“…The spectrum obtained from the sample grown on the R-plane sapphire exhibited the donoracceptor (D-A) pair emissions whose 0 th order peak was located at about 2.3 eV and two kinds of Y emission whose peaks were located at about 2.16 eV and 2.19 eV. It was reported that these Y emissions were related the recombination of excitons that were localized at extended structural defects [19]. The D-A peak was not observed from the layer grown on the S-plane substrate.…”
Section: Resultsmentioning
confidence: 98%